Formulation and Evaluation of a Sunscreen Spray Containing Butterfly Pea Flower (Clitoria ternatea) Extract as a Natural Antioxidant - Nyoman Rudi Kusuma; Nanik Sulistyani; Nining Sugihartini (Media Farmasi: Jurnal Ilmu Farmasi, 2026)
Butterfly pea flower (Clitoria ternatea) is rich in anthocyanins with recognized antioxidant activity; however, its application in spray-based sunscreen formulations and its effect on photoprotective performance remain insufficiently explored. This study aimed to formulate and evaluate a sunscreen spray containing butterfly pea extract (BPE) in combination with ethylhexyl methoxycinnamate and to determine the optimal extract concentration based on antioxidant activity, SPF value, and formulation stability. Five formulations were prepared: F0 (without BPE), F1 (0% BPE + 0.8% BHT), and F2–F4 containing 1%, 2%, and 3% BPE, respectively. Evaluations included DPPH radical scavenging activity, SPF determination, antibacterial testing, and physical quality assessment. The antioxidant activity of BPE in spray formulations showed moderate activity, with IC₅₀ values of 90.53±1.0, 87.50±1.9, and 86.94±1.4 μg/mL for 1%, 2%, and 3% concentrations, respectively, compared to 49.90±0.9 μg/mL for the pure extract. Although the antioxidant activity in formulations was lower than the pure extract due to dilution effects, increasing BPE concentration significantly improved SPF values (27.36±2.7; 29.42±1.1; 31.98±0.9; p<0.05). No significant difference was observed between 2% and 3% concentrations in both antioxidant and SPF evaluations. Therefore, 2% BPE was considered the optimal concentration, offering comparable efficacy with improved material efficiency for potential industrial production. All formulations met acceptable physical quality parameters, while antibacterial activity was not observed. This study demonstrates the feasibility of incorporating C. ternatea extract into sunscreen spray systems and provides a scientific basis for developing plant-based antioxidant-enhanced photoprotective formulations.